If ' z ' is greater than ' 1 ', then ' z ' is. If ' z ' is less than ' 1 ', then ' 1 ' is.
(z=-3) and (z=7)
The only common factor to all terms is yz. → xy³z² + y²z + xyz = yz(xy²z + y + x)
Thee of them which are 14x, -x and 2x = 15x
To find the Greatest Common Factor (GCF) of the given literal terms xxyyyzz and xxxxzzz, we need to identify the highest power of each variable that appears in both terms. In this case, the common factors are x, z, and z. The GCF of xxyyyzz and xxxxzzz is xz.
z^2
This is a difference of two sqaures. 49y2 - z2 = (7y - z)(7y + z)
6xyz(3x + 2y + z)
If ' z ' is greater than ' 1 ', then ' z ' is. If ' z ' is less than ' 1 ', then ' 1 ' is.
4z squared (z+4) (z+4)
156 your welcome
x squared + y squared = z squared.
(z=-3) and (z=7)
(z-9)(z+3
No.
re x and y and hypotenuse z then x squared + y squared = z squared If you know x and z, then y sqrd = z sqrd-x sqrd and thus y = square root of (z sqrd -x sqrd)
The only common factor to all terms is yz. → xy³z² + y²z + xyz = yz(xy²z + y + x)